Pyrite fuels electron fluxes to accelerate hydrocarbon removal in coastal wetland soil - Side Yang; Xiaolin Zhang; Kai Wang; Xiaodong Zhao; Xiaojing Li (Journal of Hazardous Materials, 2026)

Bioelectrochemical mitigation of soil antibiotic resistance: Disruption of bacteriophage transmission and resistant hosts - Feihong Zhai; Beiyi Li; Xiaodong Zhao; Pengyu Zhao; Side Yang; Xiaojing Li; Teng Wang; Geng Liu; Pingmei Yan (Journal of Environmental Sciences, 2026)

Extracellular electron transfer improves the regeneration of iron-bound organic carbon in flooding soil - Yuewei Yang; Jialu Sun; Yun Zhang; Xin Yu; Side Yang; Penghui Li; Xiaojing Li; Shungui Zhou (Geochimica et Cosmochimica Acta, 2026)

Artificial bio-cables of carbon fiber filaments bridge microbial electron flow and hydrocarbon degradation in soil - Side Yang; Xiaolin Zhang; Xiaodong Zhao; Kai Wang; Dejun Wang; Wenqing He; Xiaojing Li; Yongtao Li (Journal of Hazardous Materials, 2026)

Hexavalent chromium promotes malignant transformation via enhanced translation of SUV39H1 - Yiwei Gu; Yanan Cao; Qing Ye; Yujing Zhang; Zhishan Wang; Chengfeng Yang; Side Liu; Qing-Bai She (Chemico-Biological Interactions, 2026)

Soil photocatalysis revisited: Unveiling potential in organic contaminant remediation - Pengju Zhong; Xiaolin Zhang; Xin Yu; Side Yang; Pinpin Yang; Tian Li; Xiaodong Zhao; Xiaojing Li (Chemical Engineering Journal, 2025)

Optimizing cavitation performance in bath-type sonoreactor by numerical simulation combining the Keller-Miksis equation and nonlinear Helmholtz equation - Bowen Yang; Mingzheng Ye; Side Ren; Liyan Liu (Chemical Engineering Journal, 2025)

S–Mo conversion stimulates soil electron transfer and hydrocarbon removal for nearly one year - Jialu Sun; Xiaojuan Yi; Yuewei Yang; Yun Zhang; Xin Yu; Side Yang; Xiaolin Zhang; Ting Han; Xinhong Peng; Xiaojing Li (Chemical Engineering Journal, 2025)

Accelerating electron transfer reduces CH4 and CO2 emissions in paddy soil - Yuewei Yang; Side Yang; Jialu Sun; Yun Zhang; Xin Yu; Penghui Li; Xiaolin Zhang; Xiaojing Li (Journal of Environmental Management, 2025)

Biocurrent regulates the mercury transformation in paddy soil - Yun Zhang; Yuewei Yang; Xin Yu; Side Yang; Jialu Sun; Tao Sun; Xiaolin Zhang; Huike Ye; Yuebing Sun; Xiaojing Li (Journal of Cleaner Production, 2025)

Non-sealed water hastens the efficiency of microbial electrochemical remediation system - Iranzi Emile Rushimisha; Huike Ye; Side Yang; Xin Yu; Mohan Bai; Yali Chen; Benjamin Manirakiza; Xiaojing Li; Yongtao Li (Journal of Cleaner Production, 2024)

Fulvic acid more facilitated the soil electron transfer than humic acid - Side Yang; Kai Wang; Xin Yu; Yan Xu; Huike Ye; Mohan Bai; Lixia Zhao; Yang Sun; Xiaojing Li; Yongtao Li (Journal of Hazardous Materials, 2024)

Effect of microplastics on the degradation of tetracycline in a soil microbial electric field - Kai Wang; Side Yang; Xin Yu; Yonghong Liu; Mohan Bai; Yan Xu; Liping Weng; Yongtao Li; Xiaojing Li (Journal of Hazardous Materials, 2023)

Mitigation effects and microbial mechanism of two ecological earthworms on the uptake of chlortetracycline and antibiotic resistance genes in lettuce - Side Yang; Chenxi Lu; Cheng Qin; Chang Lu; Zheng Pan; Lixia Zhao; Mohan Bai; Xiaojing Li; Yang Sun; Liping Weng; Yongtao Li (Science of The Total Environment, 2023)

Australian wheat production expected to decrease by the late 21st century - Bin Wang; De L. Liu; Garry J. O'Leary; Senthold Asseng; Ian Macadam; Rebecca Lines‐Kelly; Xihua Yang; Anthony Clark; Jason Crean; Timothy Sides; Hongtao Xing; Chunrong Mi; et al. (Global Change Biology, 2018)
Climate change threatens global wheat production and food security, including the wheat industry in Australia. Many studies have examined the impacts of changes in local climate on wheat yield per hectare, but there has been no assessment of changes in land area available for production due to changing climate. It is also unclear how total wheat production would change under future climate when autonomous adaptation options are adopted. We applied species distribution models to investigate future changes in areas climatically suitable for growing wheat in Australia. A crop model was used to assess wheat yield per hectare in these areas. Our results show that there is an overall tendency for a decrease in the areas suitable for growing wheat and a decline in the yield of the northeast Australian wheat belt. This results in reduced national wheat production although future climate change may benefit South Australia and Victoria. These projected outcomes infer that similar wheat‐growing regions of the globe might also experience decreases in wheat production. Some cropping adaptation measures increase wheat yield per hectare and provide significant mitigation of the negative effects of climate change on national wheat production by 2041–2060. However, any positive effects will be insufficient to prevent a likely decline in production under a high CO 2 emission scenario by 2081–2100 due to increasing losses in suitable wheat‐growing areas. Therefore, additional adaptation strategies along with investment in wheat production are needed to maintain Australian agricultural production and enhance global food security. This scenario analysis provides a foundation towards understanding changes in Australia's wheat cropping systems, which will assist in developing adaptation strategies to mitigate climate change impacts on global wheat production.